2012
DOI: 10.1002/aenm.201100756
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Thermoelectric Figure of Merit by the Insertion of MgTe Nanostructures in p‐type PbTe Doped with Na2Te

Abstract: The thermoelectric properties of crystalline melt‐grown ingots of p‐type PbTe–xMgTe (x = 1–3 mol%) doped with Na2Te (1–2 mol%) were investigated over the temperature range of 300 K to 810 K. While the powder X‐ray diffraction patterns show that all samples crystallize in the NaCl‐type structure with no MgTe or other phases present, transmission electron microscopy reveals ubiquitous MgTe nanoprecipitates in the PbTe. The very small amounts of MgTe in PbTe have only a small effect on the electrical transport pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
152
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(159 citation statements)
references
References 54 publications
(80 reference statements)
6
152
0
1
Order By: Relevance
“…These are behaviors of solid solutions with statistically random atomic distribution. Recently many lead chalcogenides [31][32][33]35,36,39,[48][49][50][51] (including PbSe with PbS addition < 16%) are found with nanostructures on the <10 nm scale using TEM. These features on the nanoscale are not necessarily in conict with our SEM observation at larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…These are behaviors of solid solutions with statistically random atomic distribution. Recently many lead chalcogenides [31][32][33]35,36,39,[48][49][50][51] (including PbSe with PbS addition < 16%) are found with nanostructures on the <10 nm scale using TEM. These features on the nanoscale are not necessarily in conict with our SEM observation at larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…8,[15][16][17][18][19][20][21] When interpreting experimentally measured thermal conductivity data, researchers most often resort to a Matthiessen approach based on the phonon relaxationtime approximation 16,17,[22][23][24][25][26] assuming a single average (or effective) nanoparticle size. [10][11][12][13][14] However, recent measurements have found that in general the size of nanoprecipitates is distributed across a certain length scale ranging from ∼ 0.5 to ∼ 20 nm. [10][11][12][13][14]27 Given the fact that hierarchically architectured nanostructures scatter phonons more efficiently than monodisperse ones, 14 the underestimation of the effect of nanoparticles in previous studies is worth exploring.…”
mentioning
confidence: 99%
“…[10][11][12][13][14] However, recent measurements have found that in general the size of nanoprecipitates is distributed across a certain length scale ranging from ∼ 0.5 to ∼ 20 nm. [10][11][12][13][14]27 Given the fact that hierarchically architectured nanostructures scatter phonons more efficiently than monodisperse ones, 14 the underestimation of the effect of nanoparticles in previous studies is worth exploring. It must be noted that a very recent theoretical work showed that strongly concentrated, bimodal particle size distributions could lower the lattice thermal conductivity of SiGe beyond the single-size limit; 28 however, this kind of distribution bears little resemblance to the ones measured from experiments.…”
mentioning
confidence: 99%
See 2 more Smart Citations